2007
DOI: 10.1177/0018726707082848
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of assistant roles in the public services: Degradation or empowerment?

Abstract: This article considers whether and how shifts in the division of labour in the context of organizational change lead to the empowerment or degradation of workplace roles. It focuses on the emergence of assistants in the British public services and, in particular, whether this leads to the degradation or empowerment of those who fill the role and the professionals they work with. Concentrating upon assistant roles in education and social care, case study findings suggest that as these roles develop, the assista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 26 publications
1
37
0
Order By: Relevance
“…Existing Peer Workers had been motivated to take on the role as an opportunity to use their personal experiences to help others who shared similar problems, although managers sought to recruit those individuals who they thought would benefit most from employment as a developmental or vocational opportunity. Research into new non-professionally qualified support roles in education and social work has suggested that these roles can either become a first step on new career pathways where the work is worthwhile and satisfying, or employment ‘ghettos’ where new workers find their role to be a repository of professionals’ unwanted tasks [33,34]. Lack of a clear job description has been shown to result in allocation of task outside of the job role as perceived by Peer Workers [35].…”
Section: Discussionmentioning
confidence: 99%
“…Existing Peer Workers had been motivated to take on the role as an opportunity to use their personal experiences to help others who shared similar problems, although managers sought to recruit those individuals who they thought would benefit most from employment as a developmental or vocational opportunity. Research into new non-professionally qualified support roles in education and social work has suggested that these roles can either become a first step on new career pathways where the work is worthwhile and satisfying, or employment ‘ghettos’ where new workers find their role to be a repository of professionals’ unwanted tasks [33,34]. Lack of a clear job description has been shown to result in allocation of task outside of the job role as perceived by Peer Workers [35].…”
Section: Discussionmentioning
confidence: 99%
“…One body of research that has sought to develop our understanding of the NPA role is the word led by Kessler and Bach in the education, health and social care sectors (Bach et al ., , ; Kessler et al ., , ; see also Bach and Kessler, ; Kessler et al ., ). Four basic types of NPA worker were identified: relief, substitute, co‐producer and apprentice (Kessler et al ., ), and the basic features of each of these are set out in Table .…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Empowerment is described as being contrary to traditional management control; empowerment establishes new expectations and forms of accountability that are associated with corporate goals in conjunction with increased personal autonomy and variety (Bach et al, 2007). The responsibilization process, however, may undermine this personal autonomy.…”
Section: What Responsibilization Is Aboutmentioning
confidence: 99%